The Effect Of Entrepreneurial Education On Entrepreneurial Intention Through Innovation And Digital Literacy Of High School Students In Mojokerto Regency - Alifah, Luthfi Nur; Ludi Wishnu Wardana; Nurika Restuningdiah (International Journal of Technology and Education Research, 2025)
In this era of globalization and technological advancement, it is important for every individual to have the ability to face the challenges of an increasingly competitive world of work. One way to prepare the younger generation to face these challenges is through entrepreneurship. This study aims to explore the impact of entrepreneurial knowledge on entrepreneurial intentions through innovation and digital literacy among students at SMAN Mojokerto Regency. The research method used is the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Data analysis techniques use descriptive statistics. The results of the analysis show that (1) there is a positive and significant influence of entrepreneurial education on entrepreneurial intention, (2) there is a positive and significant influence of entrepreneurial education on innovation, (3) there is a direct positive and significant influence of entrepreneurial education on digital literacy, (4) there is a direct positive and significant influence between the innovation variable and entrepreneurial intention, (5) There is a direct positive and significant influence of digital literacy on entrepreneurial intention, (6) There is a direct positive and significant influence between entrepreneurial education and entrepreneurial intention through innovation, (7) There is a direct positive and significant influence between entrepreneurial education and entrepreneurial intention through digital literacy. The results of this study are expected to encourage educational institutions to strengthen their entrepreneurship programs by emphasizing the aspects of innovation practice and digital literacy integration. This effort will enrich students' learning experiences, shape adaptive competencies, and continuously increase their intention to become entrepreneurs in a competitive modern business environment